Studi Eksperimen Jelly Lidah Buaya Sebagai Bahan Dasar Produk Hidangan Penutup (Dessert) - Suci Sandi Wachyuni; Marya Yenny; Kadek Wiweka (Tourism Scientific Journal, 2020)
The role of dessert in one food set menu becomes very important. Currently, many cafes or restaurants sell dessert as their main menu. Dessert products are generally sweet and fresh but often have a little functional value. In this study, researchers conducted an experimental study to make dessert innovations, namely Aloe vera jelly. Jelly is widely used in restaurants or hotels as ingredients for pudding, dessert mixes, ice jelly, to various pastry toppings. Aloe vera jelly is not only refreshing but also has health value. In addition to healthy hair and skin, aloe vera is also good for our health because aloe vera contains water that is needed for the body. Aloe vera also contains fat, protein, and carbohydrates that serve to provide energy. And aloe vera also contains vitamin A and vitamin C. Where vitamin A has a function for eye health, and vitamin C has a function to maintain immunity. The purpose of this study was to find techniques and formulations for making aloe vera jelly, to know the differences in the level of preference and level of jelly quality from several levels tested based on organoleptic assessment. The method used is an experimental method with quantitative data analysis techniques ANOVA and Duncan. The results of this study indicate that the best formulation is jelly with the addition of 10% gelatin. The majority of panelists said they liked aloe vera jelly. And there is a difference in the quality of aloe vera jelly with the use of gelatin with a percentage of 5%, 10%, 15%, 20%, and 25% in aspects of color, aroma, and texture, but not different for taste.